Table of Content - - (Journal of Curriculum and Teaching Methodology, 2025)
Table of Content:1. Effectiveness of a Program Based on Differentiated Instruction for Teaching Islamic Jurisprudence in Developing Reflective Thinking Skills Among Second-Year Secondary Students in Sana'a GovernorateMr. Salim Mohsen Saleh Al-Ashwal, Prof. Muhammad Ahmed Al-Jalal, Prof. Hamid Farhan Al-Afif2. The effectiveness of blended learning using the Madrasati platform in developing critical thinking skills and developing attitudes towards it among secondary school students in the Kingdom of Saudi ArabiaDr. Fahd Ayed Al-Raddadi3. Readability Level of the First Intermediate Grade from the Point of View of Female Teachers  in the Kingdom of Saudi ArabiaMs. Nowayer Mohammed Al-Subaie4. Investing in artificial intelligence applications in teaching English at the primary levelMs. Shamma Sulimsn Aljurijeer5. The Effectiveness of the Virtual Lab in Acquiring the Periodic Movement Concepts in Physics among Grade 11 Students in Sharqiya South Governorate-Sultanate of OmanMr. Taher Jumaa Al-Salti, Prof. Osama M. Kraishan6. The Extent of future foreseeing skills inclination in the content of artificial intelligence course for the secondary stage in Kingdom of Saudi ArabiaMs. Amirah Saleh Alarawi, Prof. Najwa Atian Almohamade7. An analytical study of achievement test questions and the extent of measuring the targeted competencies in the Arabic language subject at the intermediate stageMr. Khalid Ahmed Alhazmi
Keywords: Journal of Curriculum and Teaching Methodology